EFFECTIVENESS OF DRUG PREPARATIONS AGAINST FISH NEMATODOSIS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The purpose of this research is to study the effect of Albendazole 10% and the anthelmintic drugs 2-propidamisole (powder), 2-acetamisole (powder) developed by scientists at the Institute of Plant Chemistry of the Academy of Sciences of the Republic of Uzbekistan on nematodes of the gastrointestinal tract of fish